Is electoral protection necessary to protect political rights in electoral processes? - Díaz Zegarra, Walter A. (2016)
The Peruvian constitutional justice has established that the resolutions of the JNE can be revised when they affect fundamental rights; being that the appropriate mechanism is the process of amparo; however, its use has not been effective, given that there are few cases in which it has repaired the violated right and most of the time ends up determining responsibility of the authorities that violate these rights; hence the need to assess the possibility of establishing an electoral amparo with procedures and instances different from the classic amparo.